Water use efficiency of upland rice and common bean under precision drip irrigation - Quiloango Chimarro, Carlos Alberto (2021)
The objective of this study was to quantify the water use efficiency of upland rice (Oryza sativa L.) and common bean (Phaseolus vulgaris L.) under precision irrigation management as well as the morphological and physiological responses of these crops to drought situations. The experiments were carried out under rain shelter conditions at the Biosystems Engineering Department (LEB), Sao Paulo University (ESALQ), Piracicaba SP, Brazil. In the upland rice experiment, four cultivars were tested and water depletion levels were 70 and 40%, which were imposed at two phenological stages: flowering and grain filling. In the common bean experiment, water depletion levels were 75 and 50% and irrigation strategies included long-term periods (20 DAS until the end of the crop cycle) and short-term periods (vegetative and flowering stages). Irrigation management was based on tensiometry measurements in control plots (100% of the field capacity). Irrigation depth reductions were a fraction of this control management. Under well-watered conditions, water use efficiency (WUE) for upland rice and common bean was on average of 1.4 and 1.6 kg m-3, respectively. WUE for upland rice was higher than traditional values reported in the literature, whereas for common bean it was similar to reported values for this crop under drip irrigation. WUE was not improved in any experiment under deficit irrigation strategies. Water stress occasioned significant decreases in grain yield and grain yield components of upland rice and common bean. Also, physiological traits were affected by irrigation withholding to a greater extent with the least replenishment levels. WUE derived from gas exchange measurements was not correlated with WUE measured at the end of the crop cycle. In conclusion, water use efficiency can be increased with the use of precision irrigation management, whereas irrigation deficits can affect WUE and grain productivity in both upland rice and common bean.